Dual-channel nanoelectrochemical sensor for monitoring intracellular ROS and NADH kinetic variations of their concentrations - Jiao, Yu-Ting; Jiang, Hong; Wu, Wen-Tao; Qi, Yu-Ting; Wen, Ming-Yong; Yang, Xiao-Ke; Kang, Yi-Ran; Zhang, Xin-Wei; Amatore, Christian; Huang, Wei-Hua (Biosensors & bioelectronics, 2023)
Reactive oxygen species (ROS) and nicotinamide adenine dinucleotide (NADH) are important intracellular redox-active molecules involved in various pathological processes including inflammation, neurodegenerative diseases, and cancer. However, the fast dynamic changes and mutual regulatory kinetic relationship between intracellular ROS and NADH in these biological processes are still hard to simultaneously investigate. A dual-channel nanowire electrode (DC-NWE) integrating two conductive nanowires, one functionalized with platinum nanoparticles and the other with conductive polymer, was nanofabricated for the selective and simultaneous real-time monitoring of intracellular ROS and NADH release by mitochondria in single living MCF-7 tumoral cells stimulated by resveratrol. The production of ROS was observed to occur tenths of a second before the release of NADH, a significant new piece of information suggesting a mechanism of action of resveratrol. Beyond the importance of the specific data gathered in this study, this work established the feasibility of simultaneously monitoring multiple species and analyzing their kinetics relationships over sub-second time scales thanks to dual-channel nanowire electrodes. It is believed that this concept and its associated nanoelectrochemical tools might benefit to a deeper understanding of mutual regulatory relationship between intracellular crucial molecular markers during physiological and pathological processes as well as for evaluating medical treatments. [Display omitted] •We propose a novel strategy for developing a dual-channel nanowire electrode (DC-NWE).•DC-NWE has been used for selective and simultaneous monitoring of ROS and NADH in single cells stimulated by resveratrol.•The production of ROS was observed to occur tenths of a second before NADH release.•This work presented the feasibility of simultaneously monitoring multiple species and analyzing their kinetics difference.